2005
DOI: 10.1016/j.cell.2004.11.045
|View full text |Cite
|
Sign up to set email alerts
|

A Ratchet Mechanism of Transcription Elongation and Its Control

Abstract: RNA chain elongation is a highly processive and accurate process that is finely regulated by numerous intrinsic and extrinsic signals. Here we describe a general mechanism that governs RNA polymerase (RNAP) movement and response to regulatory inputs such as pauses, terminators, and elongation factors. We show that E.coli RNAP moves by a complex Brownian ratchet mechanism, which acts prior to phosphodiester bond formation. The incoming substrate and the flexible F bridge domain of the catalytic center serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
419
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(466 citation statements)
references
References 45 publications
40
419
3
Order By: Relevance
“…The incoming nucleotide substrate acts like a pawl of a ratchet that traps the complex in its post-translocational state, which prevents the reverse motion. A related, more complex version of this model has also been proposed for multisubunit RNA polymerases (34,35). Our previous site-specific footprinting experiments with stalled HIV-1 RT complexes revealed that the presence of the templated nucleotide can stabilize and trap the post-translocated complex (27).…”
Section: Discussionmentioning
confidence: 99%
“…The incoming nucleotide substrate acts like a pawl of a ratchet that traps the complex in its post-translocational state, which prevents the reverse motion. A related, more complex version of this model has also been proposed for multisubunit RNA polymerases (34,35). Our previous site-specific footprinting experiments with stalled HIV-1 RT complexes revealed that the presence of the templated nucleotide can stabilize and trap the post-translocated complex (27).…”
Section: Discussionmentioning
confidence: 99%
“…Two mutations in the trigger loop of E. coli RNAP affect misincorporation [52]. Mutation of Rpb1 residue Glu1103 in the RNAP II trigger loop also promotes incorporation of incorrect substrates .…”
Section: Rnap Fidelity Mechanismsmentioning
confidence: 99%
“…In the "Brownian ratchet" model, random thermal fluctuations between the pre-and post-translocated states of the enzyme are mechanically rectified by NTP binding and hydrolysis, leading to unidirectional motion. Experimental (80,102) and theoretical (103,104) evidence has often been interpreted in terms of a ratchet-like mechanism, although other interpretations certainly cannot be ruled out. The power-stroke model was inspired by crystal structures of T7 RNAP obtained in nominally pre-and posttranslocated states.…”
Section: On-pathway Elongationmentioning
confidence: 99%